Testing evolutionary models to explain the process of nucleotide substitution in gut bacterial 16S rRNA gene sequences - Garcia Mazcorro, José F. (John Wiley & Sons Ltd., 2013)
The 16S rRNA gene has been widely used as a marker of gut bacterial diversity and phylogeny, yet we do not know the model of evolution that best explains the differences in its nucleotide composition within and among taxa. Over 46 000 good-quality near-full-length 16S rRNA gene sequences from five bacterial phyla were obtained from the ribosomal database project (RDP) by study and, when possible, by within-study characteristics (e.g. anatomical region). Using alignments (RDPX and MUSCLE) of unique sequences, the FINDMODEL tool available at http://www.hiv.lanl.gov/ was utilized to find the model of character evolution (28 models were available) that best describes the input sequence data, based on the Akaike information criterion. The results showed variable levels of agreement (from 33% to 100%) in the chosen models between the RDP-based and the MUSCLE-based alignments among the taxa. Moreover, subgroups of sequences (using either alignment method) from the same study were often explained by different models. Nonetheless, the different representatives of the gut microbiota were explained by different proportions of the available models. This is the first report using evolutionary models to explain the process of nucleotide substitution in gut bacterial 16S rRNA gene sequences.